2005
DOI: 10.1111/j.1365-2265.2005.02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between severity of thyroid dysfunction and renal function

Abstract: The kidney is an important target of thyroid hormone action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
162
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(190 citation statements)
references
References 18 publications
11
162
1
5
Order By: Relevance
“…Therefore, this shows that the effect of low thyroid function on creatinine metabolism in muscle and the resultant changes of serum and urinary creatinine levels are not responsible for low GFR in patients with low normal thyroid function. Causality is not conclusively determined, but it is likely that low thyroid function may reduce GFR, RPF, and RBF by increasing R a , as it has been shown that T 4 replacement therapy increases GFR in hypothyroid patients (20) and that treatment of Graves' patients with anti-thyroid drugs decreases GFR (21). Our study may also be consistent with the results that TSH positively correlated with creatinine in hypothyroid subjects (22).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, this shows that the effect of low thyroid function on creatinine metabolism in muscle and the resultant changes of serum and urinary creatinine levels are not responsible for low GFR in patients with low normal thyroid function. Causality is not conclusively determined, but it is likely that low thyroid function may reduce GFR, RPF, and RBF by increasing R a , as it has been shown that T 4 replacement therapy increases GFR in hypothyroid patients (20) and that treatment of Graves' patients with anti-thyroid drugs decreases GFR (21). Our study may also be consistent with the results that TSH positively correlated with creatinine in hypothyroid subjects (22).…”
Section: Discussionsupporting
confidence: 82%
“…In corroboration with our findings, T 3 was reported to have beneficial effects on renal function in a diabetic patient with end-stage renal failure and severe hypothyroidism (van Welsem & Lobatto 2007). Renal function was improved by T 3 in 32 patients with hypothyroidism (den Hollander et al 2005). Therefore, treatments with thyroid hormone may be an effective therapeutic approach for delaying progressive renal damage or even renal failure in diabetic patients with hypothyroidism or subclinical hypothyroidism.…”
Section: Discussionsupporting
confidence: 75%
“…The changes in biochemical markers of renal function were found to be reversible after thyroxine replacement therapy in the 46 patients who were administered thyroxine replacement. Similar changes in serum creatinine with hypothyroidism and improvement with treatment have been reported in a few scattered studies and case reports (10)(11)(12)(13). In the present study, a decrease in serum creatinine was observed in 95.65% and a decrease in uric acid was observed in 91.30% of paired values before and after treatment for hypothyroidism.…”
Section: Discussionsupporting
confidence: 56%